THE EFFECT OF COMBINATION OF NUMBERED HEAD TOGETHER AND HERRINGBONE TECHNIQUE ON EIGHTH GRADE STUDENTS’ READING COMPREHENSION AT SMP NEGERI 3 GIANYAR IN ACADEMIC YEAR 2015/2016 - ., Putu Rara Utari Dewi; ., Dr.Sudirman, M.L.S; ., Prof. Dr. Anak Agung Istri Ngr. Marha (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menyelidiki apakah ada perbedaan yang signifikan pada pemahaman membaca pada siswa kelas VIII yang diajar menggunakan kombinasi Numbered Head Together dan teknik Herringbone dengan siswa yang diajar menggunakan Numbered Head Together saja. Post-test Only Control Group digunakan sebagai desain penelitian ini. Populasi penelitian ini adalah kelas VIII di SMP Negeri 3 Gianyar. Sampel penelitian ini adalah 64 siswa yang dipilih sebagai sampel dengan menggunakan teknik sampel random atau acak. Hasil analisis menunjukkan bahwa ada perbedaan yang signifikan pada pemahaman membaca siswa kelas VIII yang diajar menggunakan kombinasi Numbered Head Together dan teknik Herringbone dengan siswa yang diajar menggunakan Numbered Head Together saja, (tobs=4.601, Sig. 0.001) dimana siswa yang diajar dengan menggunakan Numbered Head Together lebih baik pada pemahaman membaca.Kata Kunci : pemahaman membaca, Numbered Head Together, teknik Herringbone This study was aimed to investigate whether there was significance difference on eighth grade students’ reading comprehension that were taught by using combination of Number Head Together and Herringbone technique from those who were taught by using Number Head Together only. Post-test Only Control Group was used as design of this research. The population of this study was the eighth grade students of SMP Negeri 3 Gianyar. The sample of this study was 64 students that were selected as the sample of this study by random sampling. The result of analysis showed that there is significant difference on reading comprehension between students who were taught using combination Numbered Head Together and Herringbone technique and those who were taught using Numbered Head Together only, (tobs=4.601, significance 0.001) in which students who were taught using Numbered Head Together only achieved better in reading comprehension.keyword : reading comprehension, Numbered Head Together, Herringbone technique